PENGARUH STRUKTUR KEPEMILIKAN, KEBIJAKAN HUTANG, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR ENERGI DI BEI PERIODE 2018-2021 - Shela Monika; Ulil Hartono (Jurnal Ilmu Manajemen, 2023)
This study analyzes the effect of ownership structure, debt policy, and firm size on the financial performance of energy sector companies on the IDX that experience a difference between decreased ROA values and active performance of energy sector companies. Financial performance is proxied by the value of ROA. The sampling technique used a purposive sampling method so that from a population of 69 companies, 9 companies were obtained as samples. The analysis technique used is multiple linear regression. The results showed that there was a significant negative effect of debt policy on individual financial performance. However, this study did not find a significant effect of managerial ownership, institutional ownership, and company size on financial performance individually. The recommendation given is that if the company uses a debt policy proportion that is too high it will affect the decline in financial performance. Companies can reduce the proportion of their debt, by optimizing sales and utilizing internal sources for operations. Investors can use debt policies to consider in making investment decisions